Analisis Efektivitas Pemekaran Daerah Kabupaten Padang Lawas Dalam Perspektif Maqasyid Syariah - Wildan Fauzi Harahap; Imsar Imsar; Nur Ahmadi Bi Rahmani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
In its development, the new autonomous regions resulting from division did not show the expected changes. Former Director General of Regional Autonomy Djohermansyah Djohan said that of the 223 autonomous regions that were expanded in 1999-2014 80% failed to achieve the expected welfare targets. Padang Lawas district bloomed in 2007, with it the Padang Lawas district was one of the districts that was considered a failure. The purpose of this study was to find out how the effectiveness of the expansion of Padang Lawas Regency was in the perspective of Maqasyid Syariah. This study used a descriptive qualitative method by conducting interviews with informants in the form of employees of the ministry of religion, the education office, the health office, and the Padang Lawas district employment office. The results showed that the expansion of Padang Lawas Regency increased community harmony between religious communities and the development of the Islamic religion which continued to increase, services in education that were more affordable were directly proportional to the increase in community motivation in terms of intellectuals, customs and religion which still played an important role in maintaining lineage and honor by emphasizing the norms contained therein, health programs that have been realized and can be felt by the community but the problem of stunting is still a homework and more attention for the Padang Lawas district government. The division of Padang Lawas Regency has encouraged economic growth since 2009-2022 to grow by 63.11%, the labor force participation rate since 2009-2021 has increased by 14.34%.